A Comprehensive Toolkit for Inducible, Cell Type-Specific Gene Expression in Arabidopsis. Issue 1 (19th July 2018) - Schürholz, Ann-Kathrin; López-Salmerón, Vadir; Li, Zhenni; Forner, Joachim; Wenzl, Christian; Gaillochet, Christophe; Augustin, Sebastian; Barro, Amaya Vilches; Fuchs, Michael; Gebert, Michael; Lohmann, Jan U.; Greb, Thomas; et al.
Abstract : A set of transgenic lines enables spatiotemporal control of gene expression in Arabidopsis. Abstract: Understanding the context-specific role of gene function is a key objective of modern biology. To this end, we generated a resource for inducible cell type-specific transactivation in Arabidopsis ( Arabidopsis thaliana ) based on the well-established combination of the chimeric GR-LhG4 transcription factor and the synthetic pOp promoter. Harnessing the flexibility of the GreenGate cloning system, we produced a comprehensive set of transgenic lines termed GR-LhG4 driver lines targeting most tissues in the Arabidopsis shoot and root with a strong focus on the indeterminate meristems. When we combined these transgenic lines with effectors under the control of the pOp promoter, we observed tight temporal and spatial control of gene expression. In particular, inducible expression in F1 plants obtained from crosses of driver and effector lines allows for rapid assessment of the cell type-specific impact of an effector with high temporal resolution. Thus, our comprehensive and flexible method is suitable for overcoming the limitations of ubiquitous genetic approaches, the outputs of which often are difficult to interpret due to the widespread existence of compensatory mechanisms and the integration of diverging effects in different cell types.